2013
DOI: 10.1182/blood.v122.21.43.43
|View full text |Cite
|
Sign up to set email alerts
|

HBS1L-MYB intergenic Variants Modulate Fetal Hemoglobin Via Long-Range MYB Enhancers

Abstract: Three quantitative trait loci (QTLs) modifying fetal hemoglobin (HbF) levels have been identified, and these have been shown to have a predictive value of disease severity in β thalassemia and sickle cell disease in diverse ethnic groups. One of the HbF QTLs which consists of a set of common intergenic single nucleotide polymorphisms (SNPs) in the HBS1L-MYB intergenic region on chromosome 6q23, has also been consistently identified as highly associated with clinically important human erythroid traits. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…Among these associations are numerous instances where an LDB1 enhancer containing a SNP interacts with a gene relevant to the SNP phenotype whose promoter is occupied by CTCF but not LDB1 (Maurano et al, 2012). In particular, within Myb and Bcl11a enhancers, SNPs cluster at Ldb1 complex binding sites (Bauer et al, 2013;Stadhouders et al, 2014). Overall, SNPs are known to cluster at looped gene regulatory sites on a genome wide scale (Rao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among these associations are numerous instances where an LDB1 enhancer containing a SNP interacts with a gene relevant to the SNP phenotype whose promoter is occupied by CTCF but not LDB1 (Maurano et al, 2012). In particular, within Myb and Bcl11a enhancers, SNPs cluster at Ldb1 complex binding sites (Bauer et al, 2013;Stadhouders et al, 2014). Overall, SNPs are known to cluster at looped gene regulatory sites on a genome wide scale (Rao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…BCL11A appears to be a promising target for therapeutic HbF induction and recent work has shown that humans with haploinsufficiency of this gene have substantial persistence of HbF, although there appear to be adverse neurodevelopmental phenotypes found in such patients, which emphasizes the need to develop targeted approaches to suppress BCL11A (Basak et al, 2015). GWAS studies have also implicated the transcription factor, MYB, as a regulator of HbF levels and reduction of this factor does appear to robustly induce HbF production, although its mechanism of action remains unknown Stadhouders et al, 2014). Additionally, rare mutations in KLF1 have been associated with increased HbF levels in some patients, but the effects are variable and certain mutations in this factor have been associated with both increased HbF and congenital anaemias (Sankaran & Orkin, 2013).…”
Section: Developmental Switching Of Haemoglobinmentioning
confidence: 99%
“…Mouse erythroleukaemia cells have been particularly valuable in broadening our understanding of certain aspects of gene regulation, particularly given their adult globin gene expression pattern (Bauer et al, 2013). Human erythroleukaemia cell lines, including TF-1, which is cytokine responsive, and K562 cells, which are cytokine independent, have also proven to be valuable models (Sankaran et al, 2012a;Stadhouders et al, 2014;Ulirsch et al, 2014). More recently, immortalized human erythroid cell lines have been created through a variety of methods, and some of these lines may be valuable in future studies (Kurita et al, 2013).…”
Section: Cellular Modelsmentioning
confidence: 99%
“…This SNP is known to be in linkage disequilibrium with rs66650371, a 3 bp deletion at HMIP, which has been reported as the most significant motif accounting for HMIP modulation of HbF. [29][30][31][32] It is located near the erythroid-specific DNase I hypersensitivity site 2 within HMIP block 2, in close proximity to the binding sites for erythropoiesisrelated transcription factors TAL1, E47, GATA2, and RUNX1. 13 In the present study, MAF of rs9399137 is 0.137, which is among the highest frequencies observed in SCD populations (Table 3).…”
Section: Americans and Is Intermediate Between The Lower Rates Repormentioning
confidence: 99%